New Brazilian lines of Habanero pepper (Capsicum chinense): Morpho-agronomic and biochemical characterization in different environments - Soares, Renato Silva [UNESP]; Ribeiro, Cláudia Silva da Costa; Ragassi, Carlos Francisco; de Carvalho, Sabrina Isabel Costa; Maldonade, Iriani Rodrigues; Filho, José Getúlio da Silva; Braz, Leila Trevisan [UNESP]; Reifschneider, Francisco José Becker (Elsevier, 2020)
Habanero pepper is known for the diversity of its morphological characteristics and its biochemical attributes. The growth of international demand for this type of pepper is an additional opportunity for Brazilian farmers and processing industries. In order to meet this demand, it is necessary to develop new cultivars with high fruit quality and adaptation to the Brazilian growing conditions. The objective of this study was to carry out a morpho-agronomic and biochemical characterization of new lines of Habanero pepper cultivated in different environments, and to investigate the genotype x environment interaction, aiming to provide subsidies for the registration process of the new cultivars, and their subsequent release. Three advanced endogamic lines and two commercial cultivars, as control, were grown in three different growing environments, two in open field and one in protected environment. The characterization of the lines was based on nine morpho-agronomic and nine biochemical descriptors and field-incidence of the five main virus diseases. The three new lines presented important and desirable characteristics such as high yield, adequate plant size (100.0–150.0 cm) and superior quality of fruits in protected environment (CNPH 15,744); open field cultivation potential with high yield (35.0 to 40.0 t ha−1; CNPH 15,749 and CNPH 15,740); and superiority for fruit characteristics, lower total titratable acidity (15–22 %) and absence of Potato virus Y (CNPH 15,740). CNPH 15,740, CNPH 15,744 and CNPH 15,749 lines present the potential to be submitted to the cultivar registration process, mandatory in the Brazilian agricultural system, and released as new Habanero pepper cultivars developed in and adapted to Brazil, increasing the options for pepper value chain and for intermediate and final consumers. CNPH 15,744 presented unique sensory qualities for a C. chinense Habanero.
Keywords: Chile pepper; Cultivars registration; New cultivars; Open field; Protected environment; Sensory qualities